The Primacy Effect in Impression Formation: Some Replications and Extensions. Issue 4 (May 2019) - Sullivan, Jessica
Individuals described as "fun, witty, and vicious" are typically rated more favorably than those described as "vicious, witty, and fun" despite the semantic equivalence of these statements. This is known as the primacy effect in impression formation. We tested whether these effects emerge from pragmatic inferences about communicative intentions (e.g., that communicators should relay the most important information first). Participants heard a list of descriptors, with the most positive adjective listed either first or last; they also learned either that (a) the list was compiled by a human (licensing the inference that the most important information should be conveyed first) or (b) randomly ordered by a computer (thus blocking such an inference). Across five experiments (total N = 2, 882), we found support for a small primacy effect in impression formation, but found no evidence of a pragmatic explanation for primacy effects.